PENGARUH KEGIATAN FINGER PAINTING TERHADAP KETERAMPILAN MOTORIK HALUS PADA ANAK USIA 5-6 TAHUN DI PAUD ALFIAH ATHFAL MEDAN KOTA: THE INFLUENCE OF FINGER PAINTING ACTIVITIES ON FINE MOTOR SKILLS IN CHILDREN AGED 5-6 YEARS AT PAUD ALFIAH ATHFAL MEDAN CITY - Meisarah Meisarah; Darajat Rangkuti (Program Studi PG-PAUD Universitas PGRI Adi Buana Surabaya, 2023)
Based on this research, there is a significant effect of finger painting activities on fine motor skills of children aged 5-6 years at PAUD Alfiah Athfal Medan Kota T.A 2022/2023. This study used a Pre-Experimental method with a quantitative approach and a one-group pre-test-post-test research design. One group of children was treated with finger painting activities, and comparisons were made between conditions before and after treatment. To collect data, fine motor skills observation sheet instruments were used in accordance with the indicators to be achieved. The population and sample of this study were 15 children consisting of 8 boys and 7 girls. The results showed that the average pre-test score was 5.6, while the post-test score was 9.53. Data analysis was carried out using statistical tests, namely data normality tests and hypothesis tests. Based on the test results, the calculated t value is 3.64, while the t table value (2.154) with degrees of freedom (n-1) = 14. With a significance level of α = 0.05, it can be concluded that t count> t table. Therefore, the null hypothesis (Ho) is rejected, and (Ha) is accepted. Overall, this study shows that finger painting activities have a significant effect on the fine motor skills of children aged 5-6 years. This can be the basis for expanding the use of different and more interesting learning methods in improving children's fine motor development in the Alfiah Athfal Medan Kota PAUD environment.